Aspects of the design process in generative design: case study Orquestra Vermelha - Belluzzo de Campos, Gisela; Pereira Espíndola, Fabio (Revista Vazantes, 2020)
This article aims to analyze the process of projecting (creating) the work entitled Orquestra Vermelha (2013), by visual artist and musician Matheus Leston. The work, characterized by the author as “show” is a “hybrid” between installation and performance updated in real time due to use of generative design which also allows for collaboration of work and the creation of graphic and sound patterns. The methodology for writing the article consisted of project description based on the use of software, concepts of visual language, sound language, artistic performance, as well as in an interview with the author of the work.